2010
DOI: 10.1037/a0020602
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness outcomes of four age versions of the Strengthening Families Program in statewide field sites.

Abstract: Family dysfunction is unacceptably high nationally and internationally with high costs to society in adolescent problems. A number of evidence-based (EB) parenting and family interventions have been proven in research to improve children's outcome. The question remains whether these EB family programs are as effective in practice. This article summarizes research outcomes from a quasi-experimental, 5-year statewide study of the 14-session Strengthening Families Program (SFP) with over 1,600 high-risk families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 44 publications
(53 reference statements)
4
82
0
2
Order By: Relevance
“…A range of studies have reported on the effectiveness of the SFP. A quasi-experimental 5-year study using a retrospective pre/posttest parental questionnaire found medium to high effects for child-only, parent-only, and child-parent outcomes across three different age groups (Kumpfer, Greene, Whiteside, & Allen, 2010). The strongest effects were found for children between the ages of 6 and 11 years old.…”
Section: The Mate-tricks Programmentioning
confidence: 99%
“…A range of studies have reported on the effectiveness of the SFP. A quasi-experimental 5-year study using a retrospective pre/posttest parental questionnaire found medium to high effects for child-only, parent-only, and child-parent outcomes across three different age groups (Kumpfer, Greene, Whiteside, & Allen, 2010). The strongest effects were found for children between the ages of 6 and 11 years old.…”
Section: The Mate-tricks Programmentioning
confidence: 99%
“…This cost effective intervention was adapted culturally to increase its engagement and acceptability (44,45) and can be delivered in individual or group format with two levels of potency (i.e., high-risk families may participate in 14 weekly sessions, whereas lower-risk families may participate in seven weekly sessions). After being utilized with over 1,600 families, research suggested that the SFP increases positive parenting behaviors (e.g., involvement), family functioning (e.g., communication), and parental efficacy and decreases parents' substance use and depression, corporal punishment, and children's behavior problems (43,46). The largest effect sizes (d =0.77) were found for families with children who were 6-11 y of age (43), although future work should examine the appropriateness of this intervention with families of younger children.…”
Section: Skill-based Parenting Interventionsmentioning
confidence: 99%
“…After being utilized with over 1,600 families, research suggested that the SFP increases positive parenting behaviors (e.g., involvement), family functioning (e.g., communication), and parental efficacy and decreases parents' substance use and depression, corporal punishment, and children's behavior problems (43,46). The largest effect sizes (d =0.77) were found for families with children who were 6-11 y of age (43), although future work should examine the appropriateness of this intervention with families of younger children. Overall, though, in a sample of parents who were substance-involved and receiving child welfare services, 47% of these parents achieved reunification with their children (47).…”
Section: Skill-based Parenting Interventionsmentioning
confidence: 99%
See 2 more Smart Citations